2020
DOI: 10.1021/acscatal.0c04360
|View full text |Cite
|
Sign up to set email alerts
|

NADH Regeneration: A Case Study of Pt-Catalyzed NAD+ Reduction with H2

Abstract: This study shows the importance of resolving catalytic performance in the regeneration of the reduced form of nicotinamide adenine dinucleotide (NADH) through activity measurements based on NAD+ conversion and the closure of mass balance via byproduct quantification. This approach is applied to assess the performance of supported platinum catalysts with varying points of zero charge, utilizing H2 as a reductant. It was found that Pt/SiO2, which exhibits a net negative charge under the reaction conditions, outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 43 publications
2
56
0
Order By: Relevance
“…This means a hydride is added to the carbon in position 4 of the aromatic cycle of NAD + . NAD + can also be reduced at two further positions, the second and the sixth, thus leading to 1,2‐NADH and 1,6‐NADH respectively [84]. (B) Within 4 h, NAD + is reduced to 1,4‐NADH as monitored via 1 H‐NMR.…”
Section: Resultsmentioning
confidence: 99%
“…This means a hydride is added to the carbon in position 4 of the aromatic cycle of NAD + . NAD + can also be reduced at two further positions, the second and the sixth, thus leading to 1,2‐NADH and 1,6‐NADH respectively [84]. (B) Within 4 h, NAD + is reduced to 1,4‐NADH as monitored via 1 H‐NMR.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the selectivity under these two conditions was comparable at the initial stage, for example, 62.1% selectivity at 16.0% conversion for pH = 7.0 and 63.4% selectivity at 14.5% conversion for pH = 8.7. It has been reported that NADH underwent an acid-catalyzed hydration reaction under neutral and acid conditions. , Therefore, the low selectivity at pH = 7.0 could be related to the decay of NADH with its accumulation in the solution. The high selectivity to NADH makes Pt/ana-450 a promising catalyst to couple with immobilized enzymes for biocatalysis in a heterogenous manner.…”
Section: Resultsmentioning
confidence: 99%
“…As a seminal report, Wang and Yiu demonstrated that Pt/Al 2 O 3 could catalyze NAD + hydrogenation to NADH with H + as the sole byproduct, although the yield of NADH was well below 100% . Recently, Pt/C, Pt/SiO 2 , and Pt/MgO were also tested in NAD + reduction with a more reliable biological assay being employed, and the highest selectivity of NADH was only 25.1% . In addition to Pt, Pd, Rh, Ru, Ni, Au, and Ag have also been used for NAD + hydrogenation; , however, the activity and selectivity are still not desirable.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, Wang et al reported that 1 wt% Pt/C can reduce 1 under more forcing reaction conditions (10 bar H 2 , 37 °C, pH 7), and that this provided a mixture of unknown side products in addition to 2 and 3 . 23 …”
Section: Resultsmentioning
confidence: 99%